Pengaruh pajak daerah, retribusi daerah, dan dana alokasi umum, terhadap belanja modal ( studi empiris pada kabupaten dan kota di provinsi Banten tahun 2017-2020 - Feronika Uge; Endah Finatariana (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
This study aims to determine the effect of local taxes, regional levies and general allocation funds on capital expenditures. The population of this study are cities and districts in Banten Province in 2017-2020. The number of samples obtained by using purposive sampling technique were 8 cities and regencies with observations for 4 years, where the population was data on the realization of district and city APBD in Banten Province. The test tool used to test the data is a panel data regression analysis test using Eviews version 9. This data collection technique is a literature study method, where this method is both carried out by reviewing various books, journals and other sources related to the research. using the documentation method. Where the research must collect archival data at the Central Statistics Agency of Banten Province. The research method that can be used is a quantitative method, from a series of tests carried out to produce data that can prove that simultaneously local taxes, regional levies and general allocation funds have a significant effect on capital expenditures. While partially local taxes have a significant effect on capital expenditures, meanwhile regional levies and general allocation funds have no significant effect on capital expenditures